Export and the Labor Market: a Dynamic Model with on-the-job Search - Davide Suverato (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
This paper develops a two-sector, two-factor trade model with labor market frictions in which workers search for a job also when they are employed. On the job search (OJS) is a key ingredient to explain the response to trade liberalization of sectoral employment, unemployment and wage inequality. OJS generates wage dispersion and it leads to a reallocation of workers from less productive firms that pay lower wages to more productive ones. Following a trade liberalization the traditional selection effects are more severe than without OJS and the tradable sector experiences a loss of employment, while the opposite is true for the non tradable sector. Starting from autarky, the opening to trade has a positive effect on employment but it increases wage inequality. For an already open economy, a further increase of trade openness can, however, lead to an increase of unemployment. The dynamics of labor market variables is obtained in closed form. The model predicts overshooting at the time of implementation of a trade liberalization, then the paths of adjustment follow a stable transitional dynamics.
urn:nbn:de:bvb:19-epub-20919-2
Keywords: F12; F16; E24; 330; International Trade; Unemployment; Wage Inequality; Firm Dynamics